Kønsmarkører som strategier i studerendes positioneringskampe - Christensen, Gerd (Kvinder, Køn & Forskning, 2010)
Gender markings as strategies in the students struggle for positioning. References to sex and gender can be employed in order to distribute legitimacy among participants in various situations. Through analyses of four stories, this article shows how this can be practiced among university students at project-oriented educations. On the one hand, the female students are referred to as talkative and often bursting into tears. Both conducts are considered as problematic in the project groups because they take time and focus from the work on the project. Thus, the consequence of the stories is a devaluation of the female students. The male students are on the other hand told as either poor group workers because of their preferences for playing or are having to navigate between the attractiveness of being the group leader and the illegitimate position of dominating their fellow students in the group. The conclusion of the analyses states that the stories are not only told in order to distribute legitimacy among the students, but are negotiations and reformulations of the norms of the contexts.